THE IMPACT OF ASSURANCE AND EMPATHY ON THE SATISFACTION OF THE CUSTOMERS - shukri, Sakinah mohd; kKhatibi, Ali; Azam, S.M. Ferdous (International Journal of Psychosocial Rehabilitation, 2020)
The goal of this literature is to inspect the role of assurance and empathy on the satisfaction of the customers in Malaysia. The data were collected from the customers and SPSS was used to test the hypotheses testing. The results specified that positive links among the assurance and empathy and satisfaction of the customers in Malaysia. These results are accommodating the future researchers and policymakers that they should developed the policies that enhance the customer satisfaction in the country.